The evolutionary selective advantage of HIV-1 escape variants and the contribution of escape to the HLA-associated risk of AIDS progression. - Becca Asquith (PLoS ONE)
HIV-1 escape from surveillance by cytotoxic T lymphocytes (CTL) is thought to cause at least transient weakening of immune control. However, the CTL response is highly adaptable and the long-term consequences of viral escape are not fully understood. The objective of this study was to address the question "to what extent does HIV-1 escape from CTL contribute to HLA-associated AIDS progression?" We combined an analysis of 21 escape events in longitudinally-studied HIV-1 infected people with a population-level analysis of the functional CTL response in 150 subjects (by IFNg ELISpot) and an analysis of the HIV-1 sequence database to quantify the contribution of escape to the HLA-associated rate of AIDS progression. We found that CTL responses restricted by protective HLA class I alleles, which are associated with slow progression to AIDS, recognised epitopes where escape variants had a weak evolutionary selective advantage (P = 0.008) and occurred infrequently (P = 0.017). Epitopes presented by protective HLA class I alleles were more likely to elicit a CTL response (P = 0.001) and less likely to contain sequence variation (P = 0.006). A third of between-individual variation in HLA-associated disease risk was predicted by the selective advantage of escape variants: a doubling in the evolutionary selective advantage was associated with a decrease in the AIDS-free period of 1.2 yrs. These results contribute to our understanding of what makes a CTL response protective and why some individuals progress to AIDS more rapidly than others.